Mentoring is an Intellectual Pillar of Ethnobiology - Andrew Flachs; Elizabeth A. Olson; John M. Marston; Andrew Gillreath-Brown (Ethnobiology Letters, 2019)
Ethnobiology relies on community partnerships and relationships between elders or other knowledge keepers and students. Our Society of Ethnobiology, like all academic organizations, has its own issues with discrimination and abuses of power. But more than other academic disciplines, contemporary ethnobiology is practiced with and strengthened by close, respectful working relationships. As such, we offer our thoughts on the lessons ethnobiology brings to mentorship and accountability while outlining some of the specific steps we are taking as an academic and practicing community.